1993
DOI: 10.1073/pnas.90.24.11523
|View full text |Cite
|
Sign up to set email alerts
|

In vivo suppression of immune complex-induced alveolitis by secretory leukoproteinase inhibitor and tissue inhibitor of metalloproteinases 2.

Abstract: The pulmonary tree is exposed to neutrophilderived serine proteinases and matrix metalloproteinases in inflaMmatory lung diseases, but the degree to which these enzymes participate in tissue injury remains undefined, as does the therapeutic utility of antiproteinase-based interventions. cellular matrix (4, 5). Because rat and human neutrophil proteinases display considerable homology (6), we reasoned that the rat model might afford the opportunity to assess the role of leukocyte-derived proteolytic enzymes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…In the lung, apoptosis is a common cellular reaction to an insult that can result in epithelial cell loss and fibrosis, as demonstrated in murine models of pulmonary fibrosis and LPS-induced lung injury (43,44). The pleurisy model is also characterized by a substantial level of tissue injury and apoptosis (45), as seen in this study.…”
Section: Discussionmentioning
confidence: 50%
“…In the lung, apoptosis is a common cellular reaction to an insult that can result in epithelial cell loss and fibrosis, as demonstrated in murine models of pulmonary fibrosis and LPS-induced lung injury (43,44). The pleurisy model is also characterized by a substantial level of tissue injury and apoptosis (45), as seen in this study.…”
Section: Discussionmentioning
confidence: 50%
“…At the end of the 18-hour incubation period, samples were resolved by SDS-PAGE. The presence of active enzyme was determined, based on the disappearance of the parental α1(I) and α2(I) collagen (or gelatin) bands and the appearance of lower molecular weight fragments (Mulligan et al, 1993;Varani et al, 2000). …”
mentioning
confidence: 99%
“…Mulligan et al (1993) reported that SLPI and tissue inhibitor of metalloproteinase-2 (TIMP-2) produced approximately equal inhibition of immune complexinduced permeability, hemorrhage, and neutrophil influx, but the decrease in neutrophil influx was modest (about 30%) compared with the decrease in permeability and hemorrhage. Lentsch et al (1999) found that TIMP-2 did not suppress whole lung NF-B activation in a setting where SLPI was effective.…”
mentioning
confidence: 99%